Neuroendocrine Tumors: Treatment Updates - Khagi, Simon; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Neuroendocrine tumors of the gastroenteropancreatic tract remain a difficult array of neoplasia to treat. Treatment of advanced and metastatic gastroenteropancreatic neuroendocrine tumors has traditionally been difficult with few systemic treatment options. In 2011, two new targeted therapies, everolimus and sunitinib were approved for treatment of pancreatic neuroendocrine tumor. The approval of these agents led to an enhanced interest in exploring novel agents. This can be evidenced by the fact that this is the first year that ASCO assembled related abstracts under a separate title of neuroendocrine tumor. The annual American Society of Clinical Oncology (ASCO) conference in 2013 presented four abstracts (#4030, #4031, #4032, #4136) that shed light on new therapeutic options that help target the unique pathways involved in these neuroendocrine malignancies. Image: Nuclear octreotide scintigraphy.